Radical retropubic prostatectomy - a review of the current literature and a study of 250 cases at Marmara University [Radikal retropubik prostatektomi - güncel literatür derlemesi ve son 250 vaka i̇le Marmara Tecrübesi] - (:unkn) unknown (My University, 2011)
Objective: To review the current literature of open radical retropubic prostatectomy and report the results of the last 250 open radical retropubic prostatectomies performed in our University clinic. Patients and Methods: A literature review was performed using the PubMed database with combinations of the following keywords radical prostatectomy, open retropubic, prostate cancer, complications and comorbidity. Charts of the most recent 250 consecutive patients who had undergone radical retropubic prostatectomy at the Urology Department of Marmara University School of Medicine were reviewed. Results: In 69.2% of the cases the tumor was confined within the prostate gland, whereas 30.8% of the cases had tumors with either positive surgical margins, capsular penetration, invasion of seminal vesicles or a combination of these features. Nerve-sparing radical retropubic prostatectomy patients were found to be more successful in achieving continence and erectile function in the postoperative period. Cancer progressions were experienced in 12.4% of the cases following radical retropubic prostatectomy at a mean follow-up of 53.8 months with a mean time to progression of 20.7 months. Conclusion: The three goals of radical prostatectomy; cancer control, preservation of urinary control and preservation of sexual function were achieved with the long-time experience of open radical prostatectomy.
Keywords: Comorbidity; Complications; Open retropubic; Prostate cancer; Radical prostatectomy